AKT/FOXO3A pathway: Signaling target α-Synuclein overexpression and maneb mediated neurotoxicity - Conde, Melisa Ailén (2018)
α-synuclein (α-syn) overexpression and manganese-based pesticides such as Maneb (Mb) have been both implicated as etiological factors of Parkinson‘s disease. We have previously reported the neuroprotective role of Akt/FoxO3a in amyloid β- and Fe-induced injury. In this work, we studied the role of the above-mentioned pathway in the effect of Mb and/or α-syn overexpression on IMR-32 human neuroblastoma cells. For this purpose, we exposed these neurons for different times (24-72 h) to increasing Mb concentrations (6-24 μM) and evaluated the redox status, Akt/FoxO3a subcellular localization and phosphorylation levels, and cell viability. The same parameters were evaluated in neurons stably overexpressing the wild type form of α-syn and exposed to either Mb or its vehicle. Mb exposure provoked a time- and concentration-dependent decrease in neuronal viability. This cytotoxic effect was mediated by the increase in reactive oxygen species (ROS), lipid peroxides and membrane cell permeability (LDH release). Intriguingly, Mb exposure in α-synoverexpressing neurons showed decreased ROS content and LDH release, with no changes in lipid peroxides. Mb was also found to induce changes in α-syn aggregation and phosphorylation, as measured with the intracellular probe Thioflavin S and by immunocytochemistry. On the other hand, Mb exposure and α-syn overexpression unconnectedly triggered the increase in Akt and FoxO3a nuclear localization. However, Mb exposure in α-syn overexpressing neurons enhanced FoxO3a nuclear localization without increasing cell death. We hypothesize that FoxO3a might be an α-syn target related with its unexpected protective role.